Lateral violence and lateral empowerment in relation to young Indigenous populations across the CANZUS nations: a scoping review - Yvonne Clark; Feda Ali; Anneka Bowman; Rachel Elovaris; Sarah Clark; Treena Clark; Karen L. Peterson; Naomi Thornthwaite; Imani Austin; Karen Hawke (Australian Journal of Psychology)
Objective Young Indigenous people are vulnerable to lateral violence, where negative feelings and behaviours are directed towards members within their own oppressed group. Lateral empowerment, in contrast, is where young people can promote resilience and strength and collectively prevent and repair the effects of lateral violence. The aim of this scoping review was to describe how young Indigenous people aged between 0 and 25 years across the CANZUS nations (Canada, Australia, New Zealand, and the United States) experience lateral violence particularly relating to the context and forms in which young people are experiencing it; and what mechanisms of lateral empowerment pertaining to healing programmes and interventions, address young Indigenous people’s healthy wellbeing?Methods A scoping review was conducted using the Joanna Briggs Institute (JBI) framework to search for peer-reviewed publications between January 1980 and May 2024. In total, 170 peer-reviewed publications were thematically mapped into nine themes to provide an overview of the existing literature.Results Four themes to describe how young people experience lateral violence were identified: Familial and/or community violence; Interpersonal violence victimization (IVV); Peer and gang violence and Self-harm behaviour. Five themes related to the mechanisms of lateral empowerment which included: Community informed treatment approaches; Cultural identity and resilience; Family wellbeing; Use of digital technology; and Trauma intervention.Conclusion Young Indigenous people are experiencing lateral violence in many forms. Fortunately, empowering strategies were identified that strengthen young people’s wellbeing, cultural identity, connectedness to community and country to mitigate the negative impacts of lateral violence were identified.